2015
DOI: 10.1016/j.nuclphysb.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Warped conformal field theory as lower spin gravity

Abstract: Two dimensional Warped Conformal Field Theories (WCFTs) may represent the simplest examples of field theories without Lorentz invariance that can be described holographically. As such they constitute a natural window into holography in non AdS space-times, including the near horizon geometry of generic extremal black holes. It is shown in this paper that WCFTs posses a type of boost symmetry. Using this insight, we discuss how to couple these theories to background geometry. This geometry is not Riemannian. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
203
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(216 citation statements)
references
References 100 publications
8
203
0
Order By: Relevance
“…After taking the flat limit we found that among the symmetries of the N = 1 Carroll superparticle we have a supersymmetric extension of the Lifshitz Carroll algebra [30] with dynamical exponent z = 0. The bosonic part of this algebra has appeared as a symmetry of warped conformal field theories [22].…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 3 more Smart Citations
“…After taking the flat limit we found that among the symmetries of the N = 1 Carroll superparticle we have a supersymmetric extension of the Lifshitz Carroll algebra [30] with dynamical exponent z = 0. The bosonic part of this algebra has appeared as a symmetry of warped conformal field theories [22].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…One approach is to gauge the (super) Carroll algebra and/or the Lifhsitz Carroll algebra with z = 0. In this respect we note that the gauging of the Carroll algebra as performed in [28] can be improved by imposing curvature constraints that allow to set some of the spin-connection fields equal to zero, like in [22], instead of trying to solve for all of the spin-connection fields. It would be interesting to apply this improved gauging technique to the other algebras as well.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 2 more Smart Citations
“…c We thank Diego Hofman for sharing with us the observation that a particular truncation of this action is related to the lower-spin gravity action introduced in 17 .…”
Section: Extended Bargmann Gravitymentioning
confidence: 99%